"Remember, Body": A Phenomenological Approach to the Poetry of Constantin Cavafy. Issue 2 (3rd July 2021) - Field, Roger
Abstract : Phenomenology and the poetry of Constantin Cavafy (1863–1933) seldom appear in the same sentence, and there are few such approaches to his work in English. Having set out the basis of phenomenology as proposed by Edmund Husserl and interpreted by Maurice Merleau-Ponty, the article calls for critics to acknowledge their phenomenological influences more openly. It then examines early, late, published and suppressed poems and prose by Cavafy. Alongside its restrained and cerebral nature, Cavafy's work sustains readings that place the body at the centre of experience, feeling and communication. It also notes the limits of this approach, particularly when a subjective history of the body closes it off to the other.